KELAYAKAN EKONOMI DAN PEMASARAN KAKAO DI KABUPATEN LAMPUNG SELATAN - Rio Khusnul Rizal; Ali Ibrahim Hasyim; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The purposes of this research are to analyze the economic feasibility of cocoa farming and market of cocoa.  This research is conducted in two cocoa production centers of South Lampung Regency, Merbau Mataram and Way Panji sub districts.  This research is conducted by survey method.  The first goal is analyzed by investment criteria and sensitivity rate. The second goal is analyzed by marketing chain, market structure and marketing margins.  The research results showed that at 16.31% of interest rate, the 20 years lenght of intensive cultivation of cocoa farming in South Lampung Regency deserved NPV of Rp54,631,300.84; IRR 45.66%, Net B/C Ratio 8.20; Gross B/C 1.84 and PP 5.42.  The changes were the production cost increase of 6.51%, the production quantity decrease of 6.74% and the production price decrease of 18.85%, but the farm was still in the state of intensive cocoa feasible and profitable.  There are two marketing chain in South Lampung Regency, the market structure was oligopsonistic market with the distribution of ratio profit margin (RPM) was uneven.Key words: cocoa, economic, feasible, marketing